Potential Benefits of Tryptophan Metabolism to the Efficacy of Tocilizumab in COVID-19 - Maria Laura Belladonna; Ciriana Orabona (Frontiers Media S.A., 2020)
Tocilizumab has been proposed as a means of opposing hyperinflammatory responses in intensive care patients with COVID-19. Here, we briefly discuss the potentially multiple, synergistic mechanisms whereby tocilizumab might exert therapeutic activity, mostly focusing on the production of tryptophan-derived catabolites that would result from blockade of IL-6 signaling, as contextualized to the cytokine storm occurring in COVID-19 patients.